Pemilihan Supplier Barang Elektrikal Dengan Menggunakan Metode AHP (Studi Kasus: PT Petrokopindo Cipta Selaras) - Andre Bayu Mahardika; Elly Ismiyah; Yanuar Pandu Negoro (Jurnal Serambi Engineering, 2023)
PT. Petrokopindo Cipta Selaras is a corporate entity within the business sector that operates specifically within the service industry. The successful operation of trade is contingent upon the presence of adequate assistance. Nevertheless, the firm has some challenges, particularly in the domain of electrical products procurement. Delays in the delivery of electrical goods from suppliers, specifically PT. X, PT. Y, and PT. Z, impedes the operational workflows of the company. The study employed the Analytic Hierarchy Process (AHP) methodology to conduct the research. This involved constructing a hierarchical or network structure of the problem and conducting a pairwise comparison stage afterward. The findings reveal the key factors that significantly impact the supplier selection process for electrical items at PT. Petrokopindo established a prioritization framework, wherein quality criteria were assigned the greatest weight of 45.6%. This was followed by pricing criteria, which were assigned a weight of 30.3%. The third priority was given to delivery criteria, with a weight of 14.6%. Lastly, payment criteria were assigned the lowest priority, with a weight of 9.4%. PT Z holds the highest weight, specifically 35.2%, in relation to suppliers who demonstrate exceptional performance in terms of pricing criterion, carrying a weight of 20.6%. The supplier PT. The provider PT Y achieved the least outcome, with an overall weight value of 9.3%, while the lowest weight recorded was 3.8%.